1988
DOI: 10.1051/rphysap:01988002303025100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indium on the dissociation of dislocations in GaAs at high temperature

Abstract: Dislocations have been introduced in GaAs doped with indium, by plastic deformation between 773 K and 1 373 K. Transmission electron microscope observations have shown that indium increases the width of dissociation. This can explain the reduction of as-grown dislocations in In doped GaAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…m-2. The distance between partials was the same for the various test temperatures [60]. On the contrary, for In doped GaAs with [In ] = 5 x 1019 at.cm-3 deformed at 500 °C, the S.F.E.…”
Section: Formation Of Dislocations -The Nextmentioning
confidence: 81%
See 2 more Smart Citations
“…m-2. The distance between partials was the same for the various test temperatures [60]. On the contrary, for In doped GaAs with [In ] = 5 x 1019 at.cm-3 deformed at 500 °C, the S.F.E.…”
Section: Formation Of Dislocations -The Nextmentioning
confidence: 81%
“…An even larger decrease in S.F.E. has been observed in GaAs containing 1 to 4 x 1020 at.cm-3 of In deformed between 650 and 1 000 °C [60] ; with a separation between partials of 9 ± 1 nm, the S.F.E. is 27 mJ.…”
Section: Formation Of Dislocations -The Nextmentioning
confidence: 89%
See 1 more Smart Citation
“…In consequence, the yield stress is enhanced by dislocation locking. Jiminez-Melendo et al [90] observed a decrease in the stacking fault energy when GaAs was doped with In. They explained this effect by Suzuki segregation or direct interaction between solute atoms and stacking fault making cross-slip events more unlikely.…”
Section: Steps To Prevent Dislocation Patterningmentioning
confidence: 99%
“…In consequence, the yield stress is enhanced by dislocation locking. Jiminez-Melendo et al [90] observed a decrease in the stacking fault energy when GaAs was doped with In. They explained this effect by Suzuki segregation or direct interaction between solute atoms and stacking faults making cross-slip events more unlikely.…”
Section: Dislocation Cells and Grain Boundariesmentioning
confidence: 99%